FACTORS INFLUENCING CUSTOMER SATISFACTION OF PAVILION RESTO IN DENPASAR - Agustiono, Agustiono; Gede Dika Aditya (Universitas Ciputra Surabaya, 2024)
This research is to find out the influence of product quality, perceived service quality, andperceivedvalue on customersatisfaction. This research choose a food and beverage company asthe object named Pavilion Resto. This study uses multiple linear regression with a total 120 respondents, collected from closed-ended questionnaire. The result of this study shows that perceived service quality and perceived value have a significant effect on customer satisfaction. Whereas, product quality has no significant effect on customer satisfaction.